The Use of Social Media in Islamic Education: Opportunities and Challenges in Enhancing Students’ Trust and Engagement - Malikul Habsi (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
This study examines the role of social media in enhancing students’ trust and engagement in Islamic education. Using a qualitative approach, data were collected through interviews and focus groups with students and educators. Findings indicate that engagement and trust are the strongest factors, while collaborative learning and critical awareness also contribute positively. The study highlights that social media can improve learning outcomes when used ethically, with digital literacy training essential to address misinformation and ensure responsible use.